ORANG MISKIN DI NEGERI KAYA (SEBUAH KADO TANTANGAN UNTUK PRESIDEN TERPILIH) - Husamah, Husamah (Jurnal Bestari, 2009)
Poverty have become the phenomenal problem along with the history of Indonesia as a nation. The number of poverty in 2009 is estimated to be 41,1 billion people (21,92%). In narrow sense, poverty is known as condition of having not enough money and stuffs to ensure the continuing of life. In broader sense, poverty is a multifaces and multidimentional phenomenon. Furthermore, it has variation of its own manifestation and it has limited society's rights. The main pillars of to overcome poverty are pro the poor fund, good governance and social development, and process of empowerment on micro economy as pilar of development.